Method for preparing high-voltage-resistant P2-type manganese-based layered oxide sodium-ion battery material through multi-element doping of Mg, Fe and Ni
Through Mg, Fe, Ni multi-element doping technology, high-voltage resistant P2-type manganese-based layered oxide sodium-ion battery materials are prepared, which solves the problems of capacity fading and structural instability of existing materials under high pressure and high cycle times. , achieving the effects of high voltage, high stability and high specific capacity.
Patent Information
- Application Number
- CN202411440388.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-24
AI Technical Summary
Existing sodium ion battery positive electrode materials show capacity attenuation and structural instability under high voltage and high cycle times, making it difficult to meet the needs of high energy density and long life.
Through MG, FE, and NI divergence technology, prepare high -voltage -resistant P2 -type manganese -level -level oxide sodium ion battery materials, use MG and Fe to broaden voltage width, Ni increases battery ratio, realize the high voltage and high voltage of materials and high high voltage and height stability.
This technology significantly improves the cycle stability and comparison capacity of sodium -ion battery ion electoral materials, enhances the durability of the material under high pressure, and meets the needs of high energy density and long life.
Smart Images

Figure CN119349658A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of design and preparation of positive electrode materials for sodium ion batteries, and specifically relates to a method for preparing a high-voltage resistant P2 type manganese-based layered oxide sodium ion battery material by multi-element doping of Mg, Fe and Ni, and an application of the material in the positive electrode of a sodium ion battery. Background Art
[0002] The rapid development of intelligent and environmentally friendly industrial technologies such as smartphones and green electric vehicles has made rechargeable batteries an indispensable part of modern society. Among various energy storage systems, lithium-ion batteries (LIBs) occupy a key position with their superior high energy and power density performance. However, the reserves of lithium resources are low and unevenly distributed, and most lithium-ion battery cathode materials use Co and Ni as redox centers, which are costly and toxic, and cannot meet the needs of sustainable development. In recent years, sodium-ion batteries (NIBs) have attracted widespread attention and are considered to be the most promising candidate for lithium-ion batteries because sodium has similar chemical properties to lithium and higher natural abundance. However, the radius of Na ions (0.102nm) is larger than that of Li ions (0.072nm), which significantly limits the electrochemical performance of sodium-ion electrode materials. Therefore, exploring and optimizing promising electrode materials with high capacity, high rate, cyclability, and safety are crucial for the commercial implementation of sodium-ion battery technology.
[0003] Driven by the strong demand for high energy density electrode materials, efforts have been devoted to designing and developing advanced cathode materials with high capacity and high operating voltage, including layered oxides, polyanionic compounds, and Prussian blue analogs. In particular, layered transition metal oxides Na x MO2 (M = Mn, Fe, Ni, Co, Ti, Cr, etc.) has attracted extensive attention due to its high specific capacity and similar synthesis method to lithium analogs. xMO2 can be divided into P2-type and O3-type structures. Here, P or O represents the prismatic or octahedral environment of the Na site, and the number 2 or 3 represents the repeated transition metal oxide stacking within the unit cell. Due to the higher Na content, O3-type cathodes have greater advantages than P2-type cathodes in terms of Na storage capacity. However, they suffer from severe sudden capacity decay and poor cycling stability, which is mainly due to the complex structural transformation during repeated sodium insertion / deintercalation. The P2-type phase allows direct migration between adjacent prismatic sites, thereby achieving rapid transport of sodium ions and showing better applicability. However, the available capacity of P2-type positive electrode materials is still insufficient. To solve this problem, anionic redox reactions were introduced as the counterpart reactions of sodium ions, which can trigger the battery to gain additional capacity by charging it to a higher voltage range (4.0-4.5V vs. sodium ions / sodium ions. Unfortunately, at such high voltages, cathode materials inevitably undergo electrolyte decomposition, multiphase transitions, and even oxygen loss, resulting in significant voltage hysteresis and rapid capacity decay. Element doping has become an effective means. Specifically, doping with heteroatoms can change the electronic structure of the material itself and improve conductivity; stabilize the crystal structure of the material and prevent adverse phase changes during charging and discharging. Among them, doping with heteroatoms can also adjust the electrochemical window of the material and improve the specific capacity of the battery. Despite these remarkable advances in doping with heteroatoms, there are still a few studies that attempt to construct batteries with both high high-voltage stability and high cycle stability.
[0004] The present invention proposes a multi-element doping strategy, using P2-type manganese-based layered oxide as the starting material, and simultaneously doping multiple elements, such as Mg, Fe, and Ni. Among them, Mg and Fe play the best effect on widening the voltage width, and Ni doping is used to increase the specific capacity of the battery. After the simultaneous doping of the above three elements, a sodium ion battery positive electrode material with both high voltage and high stability is prepared. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a multi-element doping strategy, using P2-type manganese-based layered oxide as the starting material, and simultaneously doping multiple elements, such as Mg, Fe, and Ni. Among them, Mg and Fe play the best effect on widening the voltage width, and Ni doping is used to increase the specific capacity of the battery. The synergistic effect of multiple elements achieves the goal of simultaneously improving voltage and cycle stability.
[0006] The technical solution proposed by the present invention is:
[0007] The present invention discloses a method for preparing a high-voltage resistant P2-type manganese-based layered oxide sodium ion battery material by multi-element doping of Mg, Fe and Ni, comprising the following steps:
[0008] (1) Manganese acetate tetrahydrate, nickel acetate tetrahydrate, magnesium acetate tetrahydrate, ferric nitrate nonahydrate and sodium acetate are dissolved in a certain amount of distilled water according to a certain ratio, and stirred continuously to completely dissolve.
[0009] (2) Add a certain amount of anhydrous sodium citrate to the above solution and stir to completely dissolve it.
[0010] (3) The solution of step (2) is transferred to an oil bath at a certain temperature and heated for a certain period of time to form a dry gel.
[0011] (4) Subsequently, the dry gel is transferred to an oven at a certain temperature for drying to obtain a precursor.
[0012] (5) The obtained precursor is ground into powder, sintered in a muffle furnace, and calcined at a certain temperature for a certain time to obtain the final sample Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2.
[0013] As a preferred solution, in step (1), the molar ratio of manganese acetate tetrahydrate, nickel acetate tetrahydrate, magnesium acetate tetrahydrate and ferric nitrate nonahydrate is 7:1:1:1; sodium acetate is added in a slightly excessive amount of 5% to 10% and dissolved in 30 to 50 mL of distilled water.
[0014] As a preferred solution, in step (2), the mass of anhydrous sodium citrate added is 3 to 5 g.
[0015] As a preferred solution, in step (3), the oil bath temperature is 80-100° C. and the reaction time is 1-10 h.
[0016] As a preferred solution, in step (4), the temperature of the oven is 100 to 150° C., and the reaction time is 1 to 10 hours.
[0017] As a preferred solution, in step (5), the high temperature heat treatment is divided into two processes, the optimal temperature of the first process is 300-500°C, the heating rate is 2-5°C / min, and the heat treatment time is 2-8h; the optimal temperature of the second process is 800-1000°C, the heating rate is 2-5°C / min, and the heat treatment time is 10-24h;
[0018] Compared with the prior art, the advantages of the technology of the present invention are:
[0019] (1) First, the doping elements can be mixed evenly in one step, and multiple elements such as Mg, Fe, Ni, etc. can be doped at the same time.
[0020] (2) Multiple element doping can play different effects. For example, Mg and Fe provide a high voltage resistance, while Ni can increase the specific capacity of the battery. Therefore, the synergistic effect of multiple elements can achieve high voltage resistance, high specific capacity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The Na prepared in Example 1 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 XRD and SEM images of O2 materials.
[0022] Figure 2 is the Na of Example 1 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 TEM image of O2 material and the corresponding EDS image.
[0023] Figure 3 The Na prepared in Example 1 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 XPS pattern of O2.
[0024] Figure 4 CV data diagram of the sodium ion batteries assembled in Example 1 and Example 4.
[0025] Figure 5 The charge and discharge curves and cycle stability diagrams of the sodium ion batteries assembled in Examples 1 and 4 at different rates.
[0026] Figure 6 Electrochemical impedance diagrams of the sodium ion batteries assembled in Examples 1 and 4 at different frequencies.
[0027] Figure 7 The non-in-situ XRD patterns of the electrode materials of the sodium ion batteries assembled in Examples 1 and 4 at different voltages. DETAILED DESCRIPTION
[0028] The present invention is described more fully below in conjunction with specific embodiments and drawings, but the present invention is not limited thereto.
[0029] The experimental methods in the following examples are all conventional methods unless otherwise specified.
[0030] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0031] Example 1
[0032] Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 Preparation of O2(NMFNMO) materials
[0033] The obtained precursor was ground into powder and sintered in a muffle furnace. The program was set to keep the temperature at 450 degrees for 6 hours and then keep the temperature at 900 degrees for 12 hours, with a heating rate of 3 degrees / minute, and finally a product sample was obtained.
[0034] (1) The precursor was prepared by the sol-gel method. 1.7156 g of manganese acetate tetrahydrate, 0.2488 g of nickel acetate tetrahydrate, 0.2145 g of magnesium acetate tetrahydrate, 0.4040 g of ferric nitrate nonahydrate and 0.5769 g of sodium acetate (sodium excess 5%) were dissolved in 30 mL of water and stirred to completely dissolve.
[0035] (2) 3 g of anhydrous citric acid was added to the above mixed solution and stirred to dissolve it.
[0036] (3) The mixed solution (2) was transferred to an 80°C oil bath and heated for 8 h until the solution formed a dry gel.
[0037] (4) The dried gel was transferred to a 120°C oven and placed for 6 h to obtain a precursor.
[0038] (5) The obtained precursor was ground into powder and sintered in a muffle furnace. The first step was set to heat at 450 °C for 6 h with a heating rate of 3 °C / min. The second step was set to heat at 900 °C for 12 h with a heating rate of 3 °C / min. Finally, the product sample Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2(NMFNMO). For comparison, Na 0.67 Mg 0.15 Fe 0.15 Mn 0.7 The preparation method of O2(NMFMO) is the same as before except that nickel acetate tetrahydrate is not added.
[0039] The prepared Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2 materials, XRD Figure 1 As shown in ab, XRD and refined XRD results show that Na 0.67 Mg 0.1 Fe0.1 Ni 0.1 Mn 0.7 O2 belongs to P2 type Na 0.58 (Ni 0.333 Mn 0.667 ) 1.95 Crystalline phase, belonging to the P63 / mmc space group.
[0040] The prepared Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 The morphology and structure of O2 materials are as follows Figure 1 As shown in cd, the SEM image shows a polygonal flake morphology, which is consistent with the hexagonal crystal morphology, and the overall size is about 5μm.
[0041] Example 2
[0042] Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 Proof of element doping of O2 materials
[0043] The Na obtained in Example 1 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 The O2 material was observed by projection electron microscopy, and it can be seen that the (100) crystal plane is exposed on the surface, the lattice spacing is 0.252nm, and the electron diffraction shows that it is a hexagonal system. The corresponding EDS results show that the Na, Mg, Fe, Ni, Mn, and O elements are evenly distributed without segregation. The above results show that the three elements Mg, Fe, and Ni can be uniformly doped.
[0044] Example 3
[0045] Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 Analysis of the elemental valence state of O2 materials The Na obtained in Example 1 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7The O2 material was analyzed by X-ray photoelectron spectroscopy. The XPS results showed that the doped Ni and Mg elements were +2 valence, which promoted the Mn element to change from Mn(III) to Mn(IV)=, and Mn(III):Mn(IV)=0.542:0.458. The advantages of low-valence doping: more Mn(IV) is produced. On the one hand, the Mn(IV)-O bond is shorter, the volume of the prepared sample is reduced, and the energy density can be improved. On the other hand, the Mn(III) content is reduced, and the remaining Mn(III) under high pressure is reduced, which can reduce the dissolution of Mn, enhance the structural stability, and improve the high-pressure resistance of the material. Disadvantages: Due to the reduction of Mn(III), the variable valence elements are reduced, and the specific capacity of the material is reduced.
[0046] Example 4
[0047] Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2 material is prepared to form electrode discs to obtain Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2 material, carbon black and polyvinylidene fluoride (PVDF) were mixed and dispersed in N-methylpyrrolidone (NMP) solution at a mass ratio of 8:1:1 to form a uniform slurry. Then, the slurry was coated on aluminum foil and dried in a vacuum oven at 100°C, and then cut into 12mm discs. The mass loading of the positive electrode is about 2.0-2.5mg / cm 2 .
[0048] Example 5
[0049] Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2 materials are used in sodium-ion batteries.
[0050] The positive electrode disc obtained in Example 4 was used as the positive electrode, metallic sodium as the negative electrode, sodium perchlorate 1.0M NaClO4 in EC:DEC=1:1Vol% and 5.0%FEC as the electrolyte, and glass fiber (Whatman, GF / D) as the separator. It was assembled into a CR2032 button-type battery in a glove box with water and oxygen concentrations below 0.1ppm. The assembled battery was left to stand for 8h before electrochemical testing.
[0051] Figure 4 for Na 0.67 Mg 0.1 Fe0.1 Ni 0.1 Mn 0.7 CV curves of O2 battery at different scan rates, according to Figure 4 From the CV curve of a, it is found that there is a peak asymmetry between 2.0-2.5V, which corresponds to the Mn valence reaction. The asymmetry may be caused by the Jan-Taylor effect. No obvious redox peak was found at 3.2-4.2V, but a rectangular bulge peak appeared. The material may have a double-layer effect to store Na. There is no obvious charge and discharge platform in the GCD curve above. At the same time, the double-layer capacitance effect also shows that the material has good structural stability. According to the CV curves at different scan rates ( Figure 4 b), it was found that the two peaks at 2.0-2.5V gradually became one. The faster the scan rate, the less time Mn valence changes to respond, tending to form a redox peak. At the same time, as the scan rate increased, the peak shape of the double-layer capacitor-like rectangular peak at 3.2-4.2V did not change, further illustrating the structural stability of the material.
[0052] Figure 5 for Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2 and Na 0.67 Mg 0.15 Fe 0.15 Mn 0.7 O2 rate performance and cycle stability. Cyclic tests were conducted in the range of 2.0-4.2V and found that after Ni was added, Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2 maintains the original Na 0.67 Mg 0.15 Fe 0.15 Mn 0.7 O2 is resistant to high-voltage cycling stability, but the specific capacity is increased by 20 mAh g -1 , the rate test also shows that Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2 not only has good rate performance, but also has a higher specific capacity than Na at each rate. 0.67 Mg 0.15 Fe 0.15 Mn 0.7 O2 has improved (1C = 100mAh g -1) After one activation, the GCD curves of the half-cells basically overlap, indicating a high degree of reversibility. At the same time, after 50 cycles, there is no obvious change in the GCD curve compared with the initial one, which once again verifies the high reversibility of the material.
[0053] Figure 6 Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2 and Na 0.67 Mg 0.15 Fe 0.15 Mn 0.7 Electrochemical impedance spectroscopy (EIS) tests were performed on the O2 assembled cells. Figure 6 a shows Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 From the EIS graph of O2 after one cycle, it can be seen that the charge transfer resistance is 520Ω. Figure 6 b shows Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 From the EIS graphs of O2 after one and five cycles, it can be seen that the charge transfer resistance further decreases after five cycles, which corresponds to the increase in capacity at the beginning of the previous cycle. Figure 6 cd respectively compared Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2 and Na 0.67 Mg 0.15 Fe 0.15 Mn 0.7 The EIS diagrams of O2 cycle one and five times show that Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 The resistance of O2 is always higher than that of Na 0.67 Mg 0.15 Fe 0.15 Mn 0.7 O2 is small, which means that the former has smaller mass transfer resistance, which is consistent with Figure 5 The specific capacity results correspond to .
[0054] The assembled battery is charged and discharged to a specific voltage and then disassembled, and its electrode is subjected to XRD test, such as Figure 7 As shown, the ex situ test of Na 0.67 Mg0.1 Fe 0.1 Ni 0.1 Mn 0.7 From the characteristic peak of O2, it can be seen that during the charge and discharge cycle, at the same voltage, the position of the characteristic peak is basically the same, indicating that the material structure has excellent reversible performance and high voltage resistance.
Claims
1. The present invention discloses a method for preparing a high-voltage resistant P2-type manganese-based layered oxide sodium ion battery material by multi-element doping of Mg, Fe, and Ni, characterized in that: The following steps are involved: (1) Manganese acetate tetrahydrate, nickel acetate tetrahydrate, magnesium acetate tetrahydrate, ferric nitrate nonahydrate and sodium acetate are dissolved in a certain amount of distilled water according to a certain ratio, and stirred continuously to completely dissolve. (2) Add a certain amount of anhydrous sodium citrate to the above solution and stir to completely dissolve it. (3) The solution in step (2) is transferred to an oil bath at a certain temperature and heated for a certain period of time to form a dry gel. (4) Subsequently, the dry gel is transferred to an oven at a certain temperature for drying to obtain a precursor. (5) The obtained precursor is ground into powder, sintered in a muffle furnace, and calcined at a certain temperature for a certain time to obtain the final sample Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2.
2. The present invention according to claim 1 discloses a method for preparing a high-voltage resistant P2-type manganese-based layered oxide sodium ion battery material by multi-element doping of Mg, Fe, and Ni, characterized in that: In the step (1), the molar ratio of manganese acetate tetrahydrate, nickel acetate tetrahydrate, magnesium acetate tetrahydrate and ferric nitrate nonahydrate is 7:1:1:1; sodium acetate is added in a slightly excessive amount of 5% to 10% and dissolved in 30 to 50 mL of distilled water.
3. The present invention according to claim 2 discloses a method for preparing a high-voltage resistant P2-type manganese-based layered oxide sodium ion battery material by multi-element doping of Mg, Fe, and Ni, characterized in that: In the step (4), the mass of anhydrous sodium citrate added is 3 to 5 g.
4. The present invention according to claim 3 discloses a method for preparing a high-voltage resistant P2-type manganese-based layered oxide sodium ion battery material by multi-element doping of Mg, Fe, and Ni, characterized in that: In the step (4), the oil bath temperature is 80-100° C., and the reaction time is 1-10 h.
5. The present invention according to claim 4 discloses a method for preparing a high-voltage resistant P2-type manganese-based layered oxide sodium ion battery material by multi-element doping of Mg, Fe, and Ni, characterized in that: In the step (5), the temperature of the oven is 100 to 150° C., and the reaction time is 1 to 10 hours.
6. The present invention according to claim 5 discloses a method for preparing a high-voltage resistant P2-type manganese-based layered oxide sodium ion battery material by multi-element doping of Mg, Fe, and Ni, characterized in that: In the step (6), the high-temperature heat treatment is divided into two processes. The optimal temperature of the first process is 300-500°C, the heating rate is 2-5°C / min, and the heat treatment time is 2-8h; the optimal temperature of the second process is 800-1000°C, the heating rate is 2-5°C / min, and the heat treatment time is 10-24h.
7. Na obtained by the preparation method according to any one of claims 1 to 6 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2, characterized in that Will Na 0.67 Mg 0.1 Fe 0.1 Ni 0.1 Mn 0.7 O2, as a sodium ion positive electrode material, achieves a significant improvement in the cycle stability of sodium ion batteries through the combined effects of multiple elements.